1997
DOI: 10.1086/310622
|View full text |Cite
|
Sign up to set email alerts
|

First Astronomical Detection of the Cumulene Carbon Chain Molecule H[TINF]2[/TINF]C[TINF]6[/TINF] in TMC-1

Abstract: The cumulene carbenes are important components of hydrocarbon chemistry in low-mass star-forming cores. Here we report the first astronomical detection of the long-chain cumulene carbene H 2 C 6 in the interstellar cloud TMC-1, from observations of two of its rotational transitions: J K,KЈ ϭ 7 1,7 3 6 1,6 at 18.8 GHz and 8 1,8 3 7 1,7 at 21.5 GHz, using NASA's Deep Space Network 70 m antenna at Goldstone, California. In addition we also observed the shorter cumulene carbene H 2 C 4 at the same position. The fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 14 publications
1
65
0
2
Order By: Relevance
“…The onset of the weak system B changes with respect to the origin band of the strong one C passing from HC 9 H + to HC 15 H + . In the case of HC 9 H + it lies on the long-wavelength side of the origin of C , while for HC 13 H + it is blueshifted, for HC 15 H + it is again to the red. The electronic spectrum of HC 11 H + ͑Fig.…”
Section: B Visible Spectral Rangementioning
confidence: 88%
See 1 more Smart Citation
“…The onset of the weak system B changes with respect to the origin band of the strong one C passing from HC 9 H + to HC 15 H + . In the case of HC 9 H + it lies on the long-wavelength side of the origin of C , while for HC 13 H + it is blueshifted, for HC 15 H + it is again to the red. The electronic spectrum of HC 11 H + ͑Fig.…”
Section: B Visible Spectral Rangementioning
confidence: 88%
“…HC 2n+1 H ͑n =3-6,9͒ have been studied in the gas-phase by means of a resonant two-color two-photon ionization technique. 19 The wavelength of the origin band of HC 13 H in the gas-phase is found at 281.82 nm and at 290.0 nm in a neon matrix. Smaller members of HC 2n+1 H ͑n =2-4͒ have been studied by ab initio CASSCF and MRD-CI methods.…”
Section: -5mentioning
confidence: 99%
“…As we use the UMIST 95 ratefile, we perform a similar analysis for this database. The observed abundances for TMC-1 and L134N are taken from Ohishi et al (1992) and Langer et al (1997). Following Terzieva & Herbst (1998b), we assume that the abundance of a given molecule is consistent with observational data if it lies within an order of magnitude of the observed abundance.…”
Section: Initial Conditions For Chemistrymentioning
confidence: 99%
“…But the existence of such substituted cumulene-containing aromatic molecules is quite plausible both from the chemical point of view (Norman et al 1999), and particularly from the astrophysical one, since they are suggested by the analysis of infrared spectra (Duley 2000) and free cumulene chains have been widely detected in molecular clouds (Cernicharo et al 1991;Langer et al 1997). Moreover it has been recently established that chains like C 2 H or C 4 H are also abundant in photodissociation regions, despite the strong UV field.…”
Section: Photoinduced Productsmentioning
confidence: 99%